Highly efficient three-phase three-level multilevel inverter employing different commutation strategies - Masaoud, A.; Hew, Wooi Ping; Mekhilef, Saad; Belkamel, H. (Turkiye Klinikleri Journal of Medical Sciences, 2016)
This paper introduces a new three-phase three-level voltage source inverter. The proposed topology constitutes the conventional three-phase two-level inverter with three bidirectional switches. For purpose of generating the appropriate switching gate signals, two different commutation strategies are suggested and analyzed. A comparison between both strategies in terms of power losses and efficiency are presented. To ensure the feasibility of the proposed configuration with its suggested commutation strategies, the prototype of the proposed inverter was manufactured and the experimental results are given.